The FONAC catalogue as a result of the FON project - Kislyuk, V.S.; Yatsenko, A.I. (Кинематика и физика небесных тел, 2005)
The technique for constructing the first version of the astrographic catalogue FONAC 1.0 based on the measurements of the FON project plates (the Golosiiv overlapping the northern sky) and the Astrographic Catalogue (Carte du Ciel) data is described briefly. The procedure of plate measurements with the PARSEC measuring machine as well as the methods of their reduction are considered. The results of comparing the FONAC 1.0 with other astrometric catalogues as well as description of the second version of the catalogue FONAC 2.0 are given. Value of the FONAC catalogue series on a background of the Post-Hipparcos astrometry is discussed.